Swine Influenza Virus and Association with the Porcine Respiratory Disease Complex in Pig Farms in Southern Brazil. (24th August 2015) - Schmidt, C.; Cibulski, S. P.; Andrade, C. P.; Teixeira, T. F.; Varela, A. P. M.; Scheffer, C. M.; Franco, A. C.; de Almeida, L. L.; Roehe, P. M.
Summary: Despite the putative endemic status of swine influenza A virus (swIAV) infections, data on the occurrence of swine influenza outbreaks are scarce in Brazil. The aim of this study was to detect and subtype swIAVs from six outbreaks of porcine respiratory disease complex (PRDC) in southern Brazil. Nasal swabs were collected from 66 piglets with signs of respiratory disease in six herds. Lung tissue samples were collected from six necropsied animals. Virus detection was performed by PCR screening and confirmed by virus isolation and hemagglutination (HA). Influenza A subtyping was performed by a real‐time reverse transcriptase PCR (rRT‐PCR) to detect the A(H1N1)pdm09; other swIAV subtypes were determined by multiplex RT‐PCR. In lung tissues, the major bacterial and viral pathogens associated with PRDC ( Pasteurella multocida, Mycoplasma hyopneumoniae, Actinobacillus pleuropneumoniae, Haemophilus parasuis and PCV2) were investigated. In some affected pigs, clinico‐pathological evaluations were conducted. Influenza A was detected by screening PCR in 46 of 66 swab samples and from five of six lungs. Virus was recovered from pigs of all six herds. Subtype A(H1N1)pdm09 was detected in four of six herds and H1N2 in the other two herds. In lung tissues, further agents involved in PRDC were detected in all cases; Pasteurella multocida was identified in five of six samples and Mycoplasma hyopneumoniae in three of six. Actinobacillus pleuropneumoniae (1/6), Haemophilus parasuis (1/6) and PCV2 (1/6) were also detected. These findings indicate that subtypes A(H1N1)pdm09 and H1N2 were present in pigs in southern Brazil and were associated with PRDC outbreaks.